Gold Nanoparticles: Controlled Assembly of Biocompatible Metallic Nanoaggregates Using a Small Molecule Crosslinker (Adv. Mater. 35/2015). (September 2015) - Van Haute, Desiree; Longmate, Julia M.; Berlin, Jacob M.
<x xml:space="preserve">Abstract</x> Nanoparticle assembly is of importance for applications ranging from medical diagnostics to solar panels. On page 5158, J. M. Berlin and co‐workers report that the use of a small molecule crosslinker allows for control of metallic nanoparticle assembly in a fashion analogous to polymerization reactions. The size of the assembled aggregates can be tuned, and they are highly homogeneous, stable, and biocompatible.